Acute Toxicity of Self-Nanoemulsifying Drug Delivery System of Ipomoea reptans Poir Leaves Extract on Female Wistar Rats - Cynthia Astiti Putri; Farida Hayati; Lutfi Chabib; Muhammad Iqbal Pangestu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Ipomoea reptans Poir has many health benefits, such as decreasing blood glucose and as an antioxidant. Self-nano emulsifying drug delivery systems (SNEDDS) are an innovation in pharmaceutical technology that minimizes drug molecules and maximizes surface area, thus increasing drug absorption. This study aimed to investigate SNEDDS of I. reptans acute toxicity in female Wistar rats. An acute toxicity test was done using a limit test of OECD 423. Female Wistar rats were divided into control and treatment groups, with three animals for each group being used per step. No animals died after they were given SNEDDS of I. reptans leaves extract at a dose of 2000 mg/kg. No toxic effect was detected at clinical examination and histopathology of the organ. SNEDDS of I. reptans leaves extract had an LD50 cut-off value of 5000 mg/kg.